Competitiveness of Pharmacies in the Reflection of Consumer Trust and Loyalty - Hortolányi, Árpád László; Domán, Szilvia (Acta Carolus Robertus, 2024)
A significant part of research related to competitiveness analyses the activities of economic actors by processing quantitative data, and only a small proportion of research deals with the understanding of so-called soft factors. At the same time, these hard-to-measure resources can form the basis of a competitiveness that lasts much longer, since they are more difficult to copy by competitors. In our research, we sought the answer to the question of how social trust and loyalty, among the soft competitiveness factors that play an important role in the life of pharmacies, are related to the consumer's place of residence, which also determines the cultural environment, and - as the results of our research confirmed - to their income, also representing their level of knowledge. The correlations between the examined factors were revealed through the consumer perception of the electronic prescription, a technical innovation that has appeared in the pharmaceutical market recently. Our secondary research revealed that an industry-wide innovation such as the social acceptance of e-prescription can exert a significant influence on consumer attitudes and, through this, on the development of trust and loyalty. During the primary research, we used a standard questionnaire to reveal consumer preferences related to trust and loyalty, which were examined in connection with the place of residence and income dimensions. Based on the analyses, we found that the trust and loyalty developed regarding pharmacies is not determined by the traditional cultural background of the consumer, but rather by their income and general social knowledge related to it.
Keywords: competitiveness; consumer preferences; loyalty; pharmaceutical market; soft factors of competitiveness; trust